2017
DOI: 10.1007/s00125-017-4248-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-184 is a downstream effector of albuminuria driving renal fibrosis in rats with diabetic nephropathy

Abstract: Aims/hypothesisRenal fibrosis is a common complication of diabetic nephropathy and is a major cause of end-stage renal disease. Despite the suggested link between renal fibrosis and microRNA (miRNA) dysregulation in diabetic nephropathy, the identification of the specific miRNAs involved is still incomplete. The aim of this study was to investigate miRNA profiles in the diabetic kidney and to identify potential downstream targets implicated in renal fibrosis.MethodsmiRNA expression profiling was investigated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 50 publications
1
45
0
2
Order By: Relevance
“…A typical characteristic of DN is excessive deposition of extracellular matrix (ECM) proteins in the mesangium and renal tubule-interstitium of the glomerulus and basement membranes. ECM accumulation subsequently leads to the expansion of mesangial matrix and thickening of the glomerular and tubular basement membranes, eventually resulting in renal fibrosis, with high morbidity and mortality rates (Hu et al, 2015;Zanchi et al, 2017). Therefore, indentation of novel interventions to prevent the progression of DN is extremely important.…”
Section: Discussionmentioning
confidence: 99%
“…A typical characteristic of DN is excessive deposition of extracellular matrix (ECM) proteins in the mesangium and renal tubule-interstitium of the glomerulus and basement membranes. ECM accumulation subsequently leads to the expansion of mesangial matrix and thickening of the glomerular and tubular basement membranes, eventually resulting in renal fibrosis, with high morbidity and mortality rates (Hu et al, 2015;Zanchi et al, 2017). Therefore, indentation of novel interventions to prevent the progression of DN is extremely important.…”
Section: Discussionmentioning
confidence: 99%
“…Also, TGF‐β can induce the activation of α‐SMA in fibroblast cells, which facilitates the shrinkage of fibrotic tissues, thus leading to ischemia and hypoxia of renal tissues . Besides, the activation of TGF‐β1 is indicative of the occurrence of DN, and therefore, the suppressed expression of TGF‐β1 and α‐SMA may alleviate renal fibrosis . Myofibroblast marker α‐SMA can be reduced by increased expression of GAS5‐AS1 to against renal fibrosis formation .…”
Section: Discussionmentioning
confidence: 99%
“…36 Besides, the activation of TGF-β1 is indicative of the occurrence of DN, and therefore, the suppressed expression of TGF-β1 and α-SMA may alleviate renal fibrosis. [37][38][39] Myofibroblast marker α-SMA can be reduced by increased expression of GAS5-AS1 to against renal fibrosis formation. 40 The overexpression of GAS5 after injection with pcDNA-GAS5 could attenuate the cardiac fibrosis and improve cardiac function through decreasing the expression of MMP2, α-SMA, and COL I.…”
Section: Discussionmentioning
confidence: 99%
“…FGF23 inhibits 1-a hydroxylase gene with consequent decreased calcitriol synthesis. The previous study shown an inverse relationship between calcitriol and renin levels [29,30].…”
Section: Discussionmentioning
confidence: 86%